Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Produk Stik Cumi Khas Pulau Saobi Kabupaten Sumenep oleh Penduduk Lokal Ditinjau dari Ekonomi Syariah - W, Windrianti; Su’eb, Mochammad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Business is one of the efforts made to find out the needs of life in order to obtain benefits carried out by the community in various business opportunities, especially culinary businesses typical of a region that must be developed, because each region certainly has typical food with a unique taste. Strategy is very important in marketing a product no matter how good the target market segmentation is, and the market position that is carried out will not work if it is not followed by the right strategy. The focus of the problem in this study is, how is the marketing strategy carried out by the Saobi squid stick marketer in increasing sales of its products. The purpose of this study is to determine how the marketing strategy for the typical squid stick product of Saobi Island is to increase sales of squid stick products. This study uses a qualitative method with a descriptive approach. Data obtained through two sources, namely primary data and secondary data. Primary data is obtained by direct interviews with the owner and the marketing department of squid stick products. While secondary data is obtained from other sources related to the research, this data is obtained from books, journals, articles and other sources. The results of the study indicate that marketing strategies using word of mouth and internet or social media such as Facebook and WhatsApp have a significant impact on increasing sales of squid stick products typical of Saobi Island, Sumenep Regency. Not only that, implementing excellent service also greatly supports attracting consumer interest in buying the product.